Productivity of Journals in the Literature on Digital Libraries Research on Africa - Harande, Yahya Ibrahim; Bichi, Kabir Garba (MiddleBelt Journal of Library and Information Science, 2016)
Many research described the nature and characteristics of journals in different disciplines, fields of study and subjects background. Despite this effort none was found focusing on digital library research on Africa and about Africa. Therefore this study exhibited the scholarly contributions and performance of journals on digital library research on Africa. Bibliometrics method was employed for this research. The study analysed research on digital libraries that appeared on the Library and Information Science Abstract (LISA) from 2000 – 2011. The findings revealed that 55 journals produced 240 journal articles, out of which only four of them (30.5%) were found to constitute core journals. This finding showed that, for a decade, there seem to be a very low research activity in the subject of digital libraries in Africa. The implication of these findings was that, these core journals could be considered for effective information services and for enhancement of information resources in the library environment.